Investigating the relationship between organizational learning and communication skills with organizational conflict in the staff of education departments in the four districts of Karaj - Seyed Mohammad Mir Kamali; Ali Qaem Montazery (Institute of Management fekrenoandish, 2020)
The aim of this study was to determine the relationship between organizational learning and communication skills with organizational conflict in the staff of the Education Department of the four districts of Karaj. The study method was correlational. The statistical population of the study included all employees of the Education Department of the four districts of Karaj. According to the statistical population, a sample of 265 people was selected by stratified random sampling. Data collection tools were Nif Organizational Learning Questionnaire (2001), Baron and Hadadi Communication Skills Questionnaire (1986), and Shirkhani Organizational Conflict Questionnaire (2011). Data analysis was performed using Pearson correlation coefficient and multiple regression test (stepwise). Findings of this study showed that there is a relationship between team learning and information skills variables with organizational conflict (P <0.05) and team learning and information skills variables have the predictive power of organizational conflict. It seems that by cultivating the spirit of learning in the organization and also improving the communication skills of employees, individual and organizational conflicts can be prevented.